Investigations of electrophysiological mechanisms related to myocardial ischaemia in hypertrophic cardiomyopathy: implications for arrhythmic risk, ECG diagnosis, and antiarrhythmic therapy - Coleman, JA (2024)
Hypertrophic cardiomyopathy (HCM) is a leading cause of sudden cardiac death in the young. Acute myocardial ischaemia (a sudden myocardial blood supply/demand mismatch) and pre-existing chronic ionic remodelling (which causes slowed cellular repolarisation) are acknowledged as two key contributors to lethal arrhythmias, but the assessment of these disease factors is absent from HCM clinical guidelines. Using multiscale modelling of cardiac electrophysiology, this thesis aimed to investigate the electrophysiological effects of myocardial ischaemia and ionic remodelling in HCM, to benefit arrhythmic risk predictions, the ECG diagnosis of ischaemia, and antiarrhythmic therapy.